Exile and Displacement in the Spiritual Poetry of Sigmund von Birken. (April 2017) - Müller, Johannes
Abstract : This article examines religious interpretations of exile and forced migration in the poetry of Sigmund von Birken (1626–1681). Birken, who experienced exile as a child, when his parents were expelled from Bohemia, addresses the episode of the Holy Family's flight to Egypt in the context of the doctrine of incarnation. Based on Johann Michael Dilherr's and Catharina Regina von Greiffenberg's exegeses of Matthew 2, Birken depicts Christ's incarnation as an act of participation in human exile from paradise. This article situates Birken's poems on "Jesus the refugee" in the context of his autobiographical writings and his self‐fashioning as a religious exile. In doing so, it shows how migrant identities were cultivated in urban literary cultures of early modern Germany. Birken played a central in Nuremberg's cultural life, and his case illustrates that belonging to the heart of the urban community was not incompatible with his self‐fashioning as a newcomer and his identification with a persecuted (Lutheran) minority.